2023
DOI: 10.1088/2053-1591/acf09b
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of corrosion-resistant surface of magnesium alloy and its performance study

Shimeng Li,
Baofu Sun

Abstract: The susceptibility of magnesium alloys to corrosion has largely hindered the wide application of magnesium alloys. a natural green non-polluting method was proposed in this study to successfully prepare a corrosion-resistant film layer with MgO as the main substance on the magnesium alloy substrate by a two-step water steam method followed by annealing treatment. The morphology, composition, structure and corrosion resistance of the coating were investigated by SEM, FTIR, XRD and electrochemical methods. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…35-0821) and β-phases (Mg17Al12, JCPDS file no. 01-1128), the diffraction peaks of 2 theta (crystallographic Miller indices) appear at 32.2 (100), 34.4 (002), 36.6 (101), 47.8 (102), 63.1 (103), 68.6 (112), 72.5 (004) and 81.5 (104), respectively [34]. Zhu et al reported the diffraction peaks of Mg and Mg17Al12 and suggested that the surface of AZ91D magnesium alloy could be covered by magnesium hydroxide (Mg(OH)2, JCPDS file no.…”
Section: Structural and Morphological Analysismentioning
confidence: 99%
“…35-0821) and β-phases (Mg17Al12, JCPDS file no. 01-1128), the diffraction peaks of 2 theta (crystallographic Miller indices) appear at 32.2 (100), 34.4 (002), 36.6 (101), 47.8 (102), 63.1 (103), 68.6 (112), 72.5 (004) and 81.5 (104), respectively [34]. Zhu et al reported the diffraction peaks of Mg and Mg17Al12 and suggested that the surface of AZ91D magnesium alloy could be covered by magnesium hydroxide (Mg(OH)2, JCPDS file no.…”
Section: Structural and Morphological Analysismentioning
confidence: 99%